2022
DOI: 10.37246/grid.957922
|View full text |Cite
|
Sign up to set email alerts
|

Covid-19 pandemi sürecinde üniversite kütüphanesinde iç hava kalitesi değerlendirmesi

Abstract: During the COVID-19 pandemic, it has been determined by studies that viruses suspend more in closed and unventilated areas, so the possibility of transmission increases. It has also known that insufficient and poor quality of indoor air causes health problems and their symptoms. Particularly, indoor air quality is a significant problem in libraries where students spend most of their time. Besides, Inadequate indoor air quality in libraries has known to cause learning difficulties, decrease in working efficienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 49 publications
(32 reference statements)
0
1
0
Order By: Relevance
“…According to the experimental results, it was observed that the 𝐶𝑂 2 concentration was below 1000 ppm thanks to the applied restrictions. Moreover, they also stated that the ventilation installation of the library should be rearranged [8]. Nese and Yetiskul (2021) studied the effects of 𝑃𝑀 10 concentration on air quality for the province of Izmir during the covid-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…According to the experimental results, it was observed that the 𝐶𝑂 2 concentration was below 1000 ppm thanks to the applied restrictions. Moreover, they also stated that the ventilation installation of the library should be rearranged [8]. Nese and Yetiskul (2021) studied the effects of 𝑃𝑀 10 concentration on air quality for the province of Izmir during the covid-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%